GOAL PROGRAMMING: OPTIMALISASI KONSUMSI PANGAN BALITA PADA KELUARGA NELAYAN - Ikeu Tanziha (Food and Nutrition Society of Indonesia, 2009)
The objective of the study was to analyze food consumption optimalization for children under five years in poor families. The study design was a cross-sectional study. Research was conducted in Grogol village, in the Gunung Jati sub district, Cirebon. Respondentswere all households that have lived in that village for under five years. The data collected include socio economic and demographic data, food expenditure and food intake. An Individual energy adequacy level was calculated by comparing actual intake to RDA (Recommended Dietary Allowances). The goal programming method was applied to analyze food consumption optimalization. The results showed that there are 23 food types for consumption in combination for one week. Per capita food expenditure is Rp 4,194.- with Q1 as a lower level and Q3 as an upper level. Goal programming is the solution giving adequate energy and protein levels between 90-110%, and > 77% for vitamins and minerals.